A Long Range Side-Scan Sonar for Use in the Deep Sea (G.L.O.R.I.A. Project) - Rusby, Stuart (The International Hydrographic Review, 2015)
This brief description of a long range side-scan sonar, developed by the National Institute of Oceanography, has been written at the request of the International Hydrographic Bureau. A more detailed paper is being written at the moment by the team responsible for its development, which will describe the system more adequately.